2022
DOI: 10.1111/nicc.12743
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the Situation‐Background‐Assessment‐Recommendation tool during nurse‐physician calls in the ICU: An observational study

Abstract: Background: Situation-Background-Assessment-Recommendation (SBAR) is a tool for structuring communication between healthcare professionals. SBAR reduces medical errors, however few studies have evaluated its quality in real practice. Aims:To describe the quality of SBAR utilization by intensive care unit (ICU) nurses during phone conversations with physicians. To assess the influence of nurses' training, professional experience, and call circumstances on this quality.Study Design: This observational study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
5
2
0
Order By: Relevance
“…Regarding items in the "Background" component, there was also a noticeable improvement following the intervention, which was also noted in a study conducted by Achrekar et al [9]. However, a lower percentage of adherence to this component was reported by Scolari et al [13]. The "Assessment" component of the SBAR form displayed the lowest percentage of improvement in this study and a similar conclusion was reported by Scolari et al [13].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding items in the "Background" component, there was also a noticeable improvement following the intervention, which was also noted in a study conducted by Achrekar et al [9]. However, a lower percentage of adherence to this component was reported by Scolari et al [13]. The "Assessment" component of the SBAR form displayed the lowest percentage of improvement in this study and a similar conclusion was reported by Scolari et al [13].…”
Section: Discussionsupporting
confidence: 89%
“…Healthcare professionals' view of the importance of the SBAR tool is highly crucial, as it directly affects their adherence to uitilizing this tool for proper patient handoff. Overall, doctors displayed a positive attitude regarding their perception of SBAR form implementation, a finding similar to previous literature reports [ 13 , 17 - 18 ]. However, a notable proportion of doctors raised issues regarding time constraints in filling the SBAR form; these issues were also reported in previous studies conducted among nurses [ 13 , 19 ], which warrants a review of the simplicity of the SBAR form structure, additionally as a number of doctors also revealed difficulty understanding the content of the SBAR form.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The other papers in this issue employ a range of methodologies to address various clinically relevant topics, namely delirium in critically ill adults 10 and children 11 ; nurse–nurse 12 and nurse‐doctor collaboration 13 and teamwork 14 ; sleep quality 15,16 ; sedation and pressure injuries 17 and ABCDE bundle implementation 18 …”
mentioning
confidence: 99%